Aging, Society, and the Life Course. - Morgan, Leslie A. (Springer Pub. Co., 2006)
As our aging population grows ever larger, it is increasingly important to understand how adults age and what we can do to provide up-to-date care to ensure their well-being as an integral part of society. Leslie Morgan and Suzanne Kunkel understand that this phenomenon is about much more than just the physical or biological aspects of growing older and have put together a comprehensive text on the impact of society and sociology on the aging process. Use this text to explore the diversity of the aging population and dispel the major stereotypes surrounding the elderly. Learn about aging throu.